ANALISIS PENGARUH ALAT PRAGA IPA UNTUK PENGUASAAN KOSA KATA PESERTA DIDIK KELAS 1 SD DALAM PROSES PEMBELAJARAN - Adya Rosa Prasasti (Universitas Muhammadiyah Metro, 2024)
Abstract: The background of this research is to determine the effect of theScience Praga Tool (APIPA) on students' vocabulary mastery. This study useddescriptive qualitative method. The population in this study in class 1 of SDNegeri 7 Metro Timur was 23 students. Apart from that, this research usesobservation and interview data collection methods. Therefore, based onresearch, it is proven that the Praga IPA Tool (APIPA) is suitable for use. It wasconcluded that the use of the Science Praga Tool (APIPA) can have an effecton vocabulary mastery of class 1 students at SD Negeri 7 Metro Timur.Therefore, using the Science Praga Tool (APIPA) is one way to master students'vocabulary.